The Effectiveness of Clinical Learning Module on Competency Achievement of Nursing Students - Arif Helmi Setiawan; Siti Nurjannah; Nur Muji Astuti (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
Introduction: Clinical learning is a very important component for nursing students to integrate theoritical with skills in real settings. However, the reality revealed that the achievement of student competency is still not fulfilled yet; this is due to the unstructured interaction between students and mentors. The purpose of this study was analyzed the competence of the clinical learning module on the competency achievement of nursing student. Methods: This research is a quasi-experiment with the pretest-posttesttwogroup research design. Research samples of students in two nursing school in Surabaya who met the criteria of 50 respondents as a treatment group and 50 respondents as a control group. The research instrument used questionnaires and clinical learning modules as well as competency achievement books. Data analysis used Wilcoxon sign ranks test and Mann Whitney test with α ≤ 0,05.Results: The results of statistical tests in the control group obtained P value 0.14 showed there were differences in achievement of competencies before and after, in the treatment group obtained P value 0.000 which means that there were differences in achievement of competencies before and after using the learning module, and the results of Mann Whitney Test obtained P 0.000 , means there is an influence of the clinical learning module on the achievement of the competence of nursing students.Conclusions: Nursing clinic learning requires interaction between students and mentors so that with this clinical learning module can effectively improve the achievement of the competence of nursing students.